Advances in development of green composites based on natural fibers: a review - Kuram, Emel (Springernature, 2022)
In general, agricultural waste is left to nature or utilized as fuel material in houses. However, such use of agricultural waste negatively influences the environment. To diminish the negative effect of agricultural waste on the environment, it can be employed as natural filler in the fabrication of green composites because of its cellulosic structure. Employing of low-value agricultural waste for the development of composites is important for the reduction of environmental problems of petro-based polymers. Green composites based on agricultural waste can replace petro-based fiber composites due to excellent mechanical properties, low cost, and low density. This work has reported recent advances in the field of natural fibers especially agricultural waste fiber based green composites. To this aim, the properties of some important agricultural wastes (almond shell, arecanut husk, argan nutshell, bambara nutshell, brewer's spent grain, buckwheat husk, corn husk, cotton burr, hazelnut shell, macadamia shell, oil palm empty fruit bunch, olive pit, orange peel and pulp, pineapple leaf, pistachio shell, potato peel, pumpkin seed husk, rice husk, sunflower husk, walnut shell, wheat bran, and yerba mate) are discussed, and detailed examples for their composites are presented from the scientific literature studies. Fabrication of these green composites and obtained results were presented. From the results, it was concluded that the elastic modulus, flexural modulus, hardness, and tensile strength improved by approximately 1.5-115%, 10.7-46%, 5-8%, and 12-212%, respectively, depending on the type of polymer and natural fibers. However, in some studies, reduction in the tensile strength was reported by about 9-44% with the addition of natural fibers. A drop in elongation at break, flexural strain, flexural strength, and impact strength was observed by approximately 10-98%, 32.8-80%, 0.03-85%, and 68.5-92%, respectively, depending on the type of polymer and natural fibers. According to these results, agricultural waste fiber based composites would find wider acceptance, and added value new applications of agricultural waste fiber based composites would provide cheaper materials for international market.
Keywords: Agricultural waste; Green composite; Natural filler; Waste management